Perception of students regarding the use of ICT and learning English - María del Rocío Carranza Alcántar; Claudia Islas Torres; Mónica Lizbeth Maciel Gómez (Universidad de Guadalajara, 2018)
The growing integration of information and communication technologies in education has involved investigating how and under what circumstances and conditions these tools support students in learning a second language. This led to exposing their perception of the use of ICT as a support for learning English. The research was carried out with a quantitative, transversal and descriptive approach. The survey was applied to 162 students enrolled in the International Business career of a Mexican public university. The results show that students perceive positively the use of technologies as support in the learning of English; are aware of how these tools can help them acquire skills to master a second language; however, they acknowledge that they have not yet managed to internalize the use of ICT, mainly those aimed exclusively at the educational process. On the other hand, they consider that platforms, such as Moodle, and some types of educational software do not favor their learning, which makes it necessary to rethink the use of these tools and turn them into a dynamic space to provide greater participation by students.